Acute Traumatic Musculotendinous Avulsion of the Flexor Pollicis Longus Tendon Treated with Primary Flexor Digitorum Superficialis Transfer: A Novel Technique of Management - Sasi, P. Kiran (Case Rep Orthop, 2016)
Traumatic musculotendinous junction avulsions are rare injuries except in avulsion amputations. They pose a significant challenge to the treating surgeon. We present a 24-year-old male who sustained an open musculotendinous avulsion of the flexor pollicis longus tendon. He was treated with primary tendon transfer using the flexor digitorum superficialis of ring finger, in flexor zone 3. The functional result at 10 months following surgery was excellent.